Fabrication and structural analysis of an epitaixal Ni/Cu(001) nanostructure on a Si substrate - Lee, S. G.; Shin, S. W.; Lee, J.; Lee, J.-H.; Song, J. H.; Choi, J.-Y.; Lee, H. H.; Lee, H. S. (KOREAN PHYSICAL SOC, 2007)
An epitaxial Ni(4.5 mn - 100 nm)/Cu nanostructure has been fabricated on a Si(001) substrate by using nanoporous anodic aluminum oxide (AAO) as a mask during evaporation. Both the nanosized Cu and Ni layers have (001) surfaces with a Ni < 110 > // Cu < 110 > // Si < 001 > in-plane relation. The Ni nanostructure is found to be less strained than the film at the same Ni thickness, which plays a crucial role in determining the magnetic anisotropy of the nanostructure. Combining a self-assembled AAO mask with a conventional evaporation method can be a potential technique, instead of traditional lithography, for the growth of various epitaxial metal nanostructures.
Keywords: ANODIC ALUMINA; MAGNETIC NANOSTRUCTURES; SELF-ORGANIZATION; ANISOTROPY; FILMS; CU(001); ARRAYS; NI